Entry and exit of firms in chile - Benavente, Jose Miguel (Estudios de Economía, 2016)
In this paper we describe the pattern of creation and destruction of Chilean firms between 1999 and 2006. In addition, we construct transition matrices among different firm sizes based on tax information. It has to be noted that the available data for this study is probably the closest to what could be considered as the Chilean population of formal firms. This is one of the major strengths of this paper. By using an econometric panel data model, we found that productive sectors with the largest economies of scale show the lowest entrance rates. At the same time, the macroeconomic environment proxied by GDP growth and unemployment rates do has an impact on the exit but not on entrance figures. But, largely what has happened in lagged exit rates directly affects contemporary entrance rates. Therefore, public policies should be aware about those who want to restart new firms rather than concentrate too much on maintaining those which are notably unproductive.